Activision Blizzard: Consolidation movements in a maturing videogame industry and value creation - Martins, Rafael Tiago Duarte (2012)
The present thesis was done with the objective to assess if the merger between Activision and Vivendi Games created value to its shareholders and if the share price used in this transaction represented the real value of this operation. This merger occurred in difficult economic times due to the financial crisis of 2007/2008 and in a period of consolidation and maturity in the videogame industry, allied to the rising costs of development and marketing that current videogames are experiencing. The main conclusion was that this merger created value for the shareholders in 2008, mainly due to increased revenues, and is likely to create more value than both companies were initially expecting, according to the present value of the expected cash flows, that were calculated with a 5 year projection for the period 2009-2013.